O agir moral na fundamentação da metafísica dos costumes e na crítica da razão prática - Silva, Hortênsia Teresa Tomaz da (2017)
The aim of this work will be to investigate how Kant explains or grounds moral action in the Groundwork of the Metaphysics of Morals and Critique of Practical Reason. Indeed, we can say that the moral action in the first is grounded on spontaneity of action give by freedom. Therefore, to show these points, the following path will be followed: in 2.1 we will see the emergence of a new conception of morality. In 2.2 we will see that the new conception interprets the morality as autonomy. In section 3 we will examine elements that characterize the nature of moral action in the GMS and in the Kantian moral philosophy. In point 3.1 we will see that Kant sustains moral action in the third section of the GMS in the idea that when we think ourselves as free we are transposed into an intelligible world, possible for freedom. We will also speak in this same subsection of the problems related to the vicious circle, the deduction of the moral law in the GMS as well as the distinction between a sensible and intelligible world. In point 4 on the factum of reason we will show the factum as being the consciousness of the moral law and as not being able to deduction. We will show that Kant sustains the moral action in the KpV on the ideia of such factum. We will also introduce in this same topic the two possible interpretations of the factum of reason. In the next subsection in 4.1 we will show Beck’s (1960) interpretation according to which we have in KpV what could formally correspond to a deduction of the moral principle. In 4.2 we will see Allison’s (1990) interpretation according to which such factum of reason can be understood as factum of reason, that is, as evidence that pure reason is practical. In 4.3 we will show that, unlike Beck (1960), Almeida (1998) will deny that a deduction of the moral law in the KpV is possible. In fact, Almeida (1998), will conclude because of this impossibility, the sense of factum of reason that would be imposed would be the cognitivist (or intuitionist) sense. In this same subsection, in view of the cognitivist interpretation we will expose Beck’s (1981) interpretation in which he rejects the cognitivist point of view. In subsection 4.4 we will see freedom as a condition of moral in the KpV and, finally, we will focus our attention on the moral feeling in the KpV.